MOTIVASI MAHASISWA MEMILIH PROGRAM STUDI ILMU KEPERAWATAN UNIVERSITAS RIAU - Sulastri "; Risdayati " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
This study aims to look at the motivation of the factors that influence the students in choosing the type of education Nursing Science in this case researchers determined the location of the research at the University of Riau which is the object of research is Student Nursing Science Program. In addition, this study also aims to determine how the student on stereotypical perceptions of the public about the nursing profession for a man. Population of this research consisted of program A and program B, the study sample was taken from the entire Student Program A, amounting to 57 people. Data collection techniques using observation techniques and questionnaires. Then the data were analyzed using quantitative descriptive method. Based on the results of the analysis found that the motivation of the students chose Nursing Science Program consists of the factors that affect the students in choosing the types of nursing education, which consists of internal factors: the interests and talents, ideals, the decision itself, and external factors: a boost parents, peers and the media. While the response of students to the stereotypical student nurse who answered ever heard public comments about the nursing profession they say the profession is not about gender, because the soul of gentle care not only of the woman but also have male. Keywords: Gender, Profession male nurse